Categorizing Practical Training Programs for New Farmers - Laura Schreiner; Charles Z. Levkoe; Theresa Schumilas (Journal of Agriculture, Food Systems, and Community Development, 2018)
Despite limited study, farmer training is an area of growing interest and concern among new and experienced farmers across North America. It is also an area with broad implications regarding the future of domestic food production. This paper presents findings from a community-campus partnership research study that aimed to explore, document, and categorize existing and emergent models of practical farmer training in North America. We begin by describing the context of practical farming and the need for training programs, followed by a discussion of our findings organized into five analytical categories along with discussion of their implications: (1) Informal farm internship associations; (2) centralized internship programs; (3) private or nonprofit course-based programs; (4) formal academic programs; and (5) independent and self-directed learning. We conclude with some implications from this study and suggest areas for future research. It is our hope that the categories presented here will provide a springboard to support the future research and development of new practical farmer training programs.